2006
DOI: 10.1016/j.devcel.2006.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin Is Necessary for Wnt-3a-Dependent Internalization of LRP6 and Accumulation of β-Catenin

Abstract: beta-catenin-mediated Wnt signaling is critical in animal development and tumor progression. The single-span transmembrane Wnt receptor, low-density lipoprotein receptor-related protein 6 (LRP6), interacts with Axin to promote the Wnt-dependent accumulation of beta-catenin. However, the molecular mechanism of receptor internalization and its impact on signaling are unclear. Here, we present evidence that LRP6 is internalized with caveolin and that the components of this endocytic pathway are required not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
339
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(365 citation statements)
references
References 47 publications
24
339
1
1
Order By: Relevance
“…4F). In line with the luciferase data, whereas the S isoform did not affect LRP6DN perinuclear localization (26,27), the L isoform expression almost abrogated LRP6DN labeling (Fig. 4G).…”
Section: Membrane-associated Tmem131l Triggers Degradation Of Phosphosupporting
confidence: 86%
“…4F). In line with the luciferase data, whereas the S isoform did not affect LRP6DN perinuclear localization (26,27), the L isoform expression almost abrogated LRP6DN labeling (Fig. 4G).…”
Section: Membrane-associated Tmem131l Triggers Degradation Of Phosphosupporting
confidence: 86%
“…Thus, endocytic vesicles are postulated to provide a platform for assembly and transport of the Axin complex to the plasma membrane for inactivation by Wnt receptors (Cliffe et al, 2003). Consistent with this model, several recent reports have demonstrated that endocytosis and endosomal transport have been shown to facilitate and maximize Wnt signaling in Drosophila (Chen et al, 2003;Yamamoto et al, 2006).…”
Section: Dab2 and Wnt Signaling Y Jiang Et Almentioning
confidence: 79%
“…Unexpectedly, Axin is also required for Wnt-induced LRP6 PPPSP phosphorylation, and Axin overexpression enhances PPPSP phosphorylation Yamamoto et al 2006), but only if Axin is not impaired in GSK3 binding . These findings led to a model that DVL binding to and recruitment of Axin into the FZD -LRP6 complex initiates GSK3 phosphorylation of LRP6 on PPPSP motifs .…”
Section: Lrp6 Phosphorylation: Kinases and Regulationmentioning
confidence: 99%
“…Another model, in which phosphorylated/ activated LRP6 signals in an endosomal platform, posits that LRP6 and phosphorylation in lipid rafts (a cholesterol-rich microdomain in the plasma membrane) and its subsequent endocytosis through caveolin are both required for signaling (Yamamoto et al 2006(Yamamoto et al , 2008. Caveolin binds to LRP6 upon Wnt stimulation and is required for phosphorylated LRP6 to recruit Axin (Yamamoto et al 2006).…”
Section: Lrp6 Signal Initiation-amplification Signalosomes and Endomentioning
confidence: 99%
See 1 more Smart Citation